1985
DOI: 10.1016/0014-5793(85)80723-7
|View full text |Cite
|
Sign up to set email alerts
|

The primary structure of transcription factor TFIIIA has 12 consecutive repeats

Abstract: Analysis of the ammo acid sequence of transcnptlon factor TFIIIA from Xenopus laevzs reveals the presence of 12 repeating structures, each about 30 residues m length These segments have been ahgned and their secondary structure predicted The repeats each contam two invariant cystemes and two invariant hlstldmes, perhaps to coordinate a zmc catlon Possible nucleic acid mteractlon modes are discussedTranscrrptlon factor TFIIIA

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
219
0
3

Year Published

1988
1988
2010
2010

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 424 publications
(225 citation statements)
references
References 18 publications
(2 reference statements)
2
219
0
3
Order By: Relevance
“…The UAS2 sequence includes the 25 bp directly upstream of UAS1 and allows ADR1-independent derepression of ADH2 expression (J. Yu, personal communication). ADR1 contains two zinc finger domains (10), similar to those which were first observed in transcription factor IIIA from Xenopus laevis, having the consensus sequence Cys-X24-Cys-X3-Phe-X5-Leu-X2-His-X2-His (5,19). Zinc finger domains have since been found in several eucaryotic genes thought to be involved in the regulation of transcription (6,18,25,29,30) and in some cases have been shown to bind DNA specifically at regulatory elements (8,15,28).…”
mentioning
confidence: 75%
“…The UAS2 sequence includes the 25 bp directly upstream of UAS1 and allows ADR1-independent derepression of ADH2 expression (J. Yu, personal communication). ADR1 contains two zinc finger domains (10), similar to those which were first observed in transcription factor IIIA from Xenopus laevis, having the consensus sequence Cys-X24-Cys-X3-Phe-X5-Leu-X2-His-X2-His (5,19). Zinc finger domains have since been found in several eucaryotic genes thought to be involved in the regulation of transcription (6,18,25,29,30) and in some cases have been shown to bind DNA specifically at regulatory elements (8,15,28).…”
mentioning
confidence: 75%
“…Mapping the details of this extensive protein-DNA interaction using chemical, biochemical, and genetic techniques has continued for almost 20 years (1-3, 9, 10). The discovery of nine zinc fingers in TFIIIA (11,12) led to the notion of a transcription factor with repeated modules in its DNA-binding domain (Fig. 1B).…”
Section: Introductionmentioning
confidence: 99%
“…It was first recognized in the Xenopus transcription factor IIIA as a conserved protein domain of 28 to 30 amino acids that contains a number of invariant residues (3,4,41). The nuclear magnetic resonance solution structure of a single zinc finger demonstrated that this motif forms a compact globular domain that is composed of an antiparallel ␤-sheet followed by an ␣-helix and is stabilized by the coordination of a Zn 2ϩ ion through two cysteine and two histidine residues (31).…”
mentioning
confidence: 99%